Retraction notice to “Use of biomass-derived biochar in wastewater treatment and power production: A promising solution for a sustainable environment” [Sci. Total Environ. 825 (2022) 153892] - Meenal Gupta; Nishit Savla; Chetan Pandit; Soumya Pandit; Piyush Kumar Gupta; Manu Pant; Santimoy Khilari; Yogesh Kumar; Daksh Agarwal; Remya R. Nair; Dessy Thomas; Vijay Kumar Thakur (Science of The Total Environment, 2026)

A review on microbial-biofilm mediated mechanisms in marine microplastics degradation - Soumyajit Chandra; Dibyajit Lahiri; Moupriya Nag; Debasmita Bhattacharya; Chetan Pandit; Soumya Pandit; Kuldeep Sharma; Mithul Rajeev; Harjot Singh Gill; Sarvesh Rustagi (Antonie van Leeuwenhoek, 2025)

Microalgal Bioethanol Production for Sustainable Development: Current Status and Future Prospects - Chetan Pandit; Soumya Pandit; Ramesh Chander Kuhad; Subhasree Ray; Santosh Kumar Mishra; Abhilasha Singh Mathuriya; Ram Prasad (Indian Journal of Microbiology, 2025)

Harnessing microbial fuel cells for mitigating metal corrosion in offshore wind power infrastructure: Mechanisms, applications, and future prospects - Siddhant Srivastava; Chetan Pandit; Hsun-Yi Chen; Chin-Tsan Wang (Chemical Engineering Journal, 2025)

Exploring the performance of biocatalysts for biohydrogen production - Chetan Pandit; Mohit Kumar; Ramesh Chander Kuhad; Kuldeep Sharma; Amit Roy; Rishikesh Shukla; Soumya Pandit; Nishant Ranjan; Santosh Kumar Mishra; Ram Prasad (Biocatalysis and Agricultural Biotechnology, 2024)

Wired for energy: Electromethanogenesis redefining anaerobic digestion - Soumya Pandit; Chetan Pandit; Abhilasha Singh Mathuriya; Soumya Chatterjee; Dipak A. Jadhav; Krishna Kumar Yadav; Mohammad Khalid (Process Safety and Environmental Protection, 2024)

A concise review on biorefinery remedies for biomethanol production and processing - Mayur Thakare; Soumya Pandit; Chetan Pandit; Subhasree Ray; Abdullah M. Alkahtani; Khulood Fahad Alabbosh; Nishant Ranjan; S.J. Geetha; Sanket J. Joshi (Biocatalysis and Agricultural Biotechnology, 2024)

Degradation of food dyes via biological methods: A state-of-the-art review - Vandana Singh; Chetan Pandit; Arpita Roy; Soumya Pandit; Ashutosh Kumar Rai; Anju Rani; Nishant Ranjan; Sarvesh Rustagi; Sumira Malik (Bioresource Technology Reports, 2024)

Life cycle assessment of revalorization of lignocellulose for the development of biorefineries - Srijoni Banerjee; Chetan Pandit; Marttin Paulraj Gundupalli; Soumya Pandit; Nishant Rai; Dibyajit Lahiri; Kundan Kumar Chaubey; Sanket J. Joshi (Environment, Development and Sustainability, 2023)

Microalgal pandora for potent bioenergy production: A way forward? - Srijoni Banerjee; Dipankar Ghosh; Chetan Pandit; Sagnik Saha; Anwesha Mohapatra; Soumya Pandit; Minaxi Sharma; Kandi Sridhar; Baskaran Stephen Inbaraj; Ram Prasad (Fuel, 2023)

Illuminating the signalomics of microbial biofilm on plant surfaces - Sanchita Bipin Patwardhan; Chetan Pandit; Soumya Pandit; Devvret Verma; Dibyajit Lahiri; Monupriya Nag; Rina Rani Ray; Priyanka Jha; Ram Prasad (Biocatalysis and Agricultural Biotechnology, 2023)

Community-Based Forest Enterprises in Nepal: An Analysis of Their Role in Increasing Income Benefits to the Poor - Bishnu Hari Pandit; Adrian Albano; Chetan Kumar (Small-scale Forestry, 2009)

A new paradigm for R&D in water resources engineering - Chetan Pandit (Irrigation and Drainage, 2003)
The technology in water resources engineering (WRE) seems to be stagnant. No new technology of any significance has emerged for quite some time now and there seems to be none in the pipeline. In the WRE sector, R&D does not generate the same level of excitement and challenges that it does in other sectors. Shortage of funds does not seem to be the reason for this disappointing performance of R&D. The main problems are: WRE R&D has very little potential for patents, Intellectual Property Rights (IPR) and profit and therefore the private sector does not take any interest in R&D in WRE. Most of the research pursued by the universities is too theoretical. There is very little applied research. There is a marked lack of creativity and inspiring ideas for R&D. There are neither any “technology dreamers” nor any dreams. Users are not being involved in the planning. The time is running out for R&D managers in WRE. The vision plans of most governments incorporate a set of measurable performance targets to be achieved in a stipulated time frame. Many of the targets are less than 10 years away. Therefore, if R&D is to be of any assistance in achieving the targets set for 2010, then that R&D must start now, not next year. The present approach to R&D has not produced desired results and, therefore, it must be changed immediately. The paper proposes a new approach to provide an impetus to R&D in the WRE sector. Copyright © 2003 John Wiley & Sons, Ltd.